Poroma: A case report of pulsatile papule visualized on dermoscopy - Thanadon Eksomtramage; Kumpol Aiempanakit (Clinical Case Reports, 2019)
Abstract Poroma, a benign sweat tumor, commonly presents with a nontender papule on the extremities. It can appear with a blinking light appearance on dermoscopy in real time.